Yield and Quality Features of Buckwheat-Soybean Mixtures in Organic Agricultural Conditions - Mustafa Sürmen; Emre Kara (Turkish Journal of Agriculture: Food Science and Technology, 2017)
This study was carried out during the summer of 2014 to determine alternative quality forage sources that could be grown in the Aydın ecological conditions. In the study, effects of 3 different mixtures and 2 pure species (100% Buckwheat, 25% Buckwheat -75% Soybean, 50% Buckwheat -5 0% Soybean, 75% Buckwheat - 25% Soybean, 100% Soybean) and 2 different harvesting times (50%-100% flowering/buckwheat) on yield and quality characteristics were investigated. According to measurements, the highest average herbage yield was obtained from 75% Buckwheat-25% Soybean application (3100 kg/da) at 2nd harvest time. When the average of hay yield was examined, the results were similar to herbage yield. When ADF and NDF were examined, the highest values were seen at the 2nd harvest. When the crude protein ratios were examined, it was found that they decreased at the 2nd harvesting time and the highest value was determined at 100% soybean application at the 1st harvesting time (21.08%). When Digestible Dry Matter (DDM) and Relative Feed Value (RFV) were examined, the highest values were determined in 100%Soybean applications at first harvest time and when the mixture applications were examined, the highest values were determined to be 75% Buckwheat - 25% Soybean application. As a result of the study, it was determined that the yields obtained at the 2nd harvest time were higher but the forage quality decreased. When the mixtures were examined, it was determined that the mixture having the highest roughage value was 75% buckwheat + 25% soybean application. In this study, the buckwheat which have short vegetation and good quality and the soybean, which is infront of with high quality, mixtures were examined. It has also been found that these mixtures may be important for obtaining high-quality forage in the short and intermediate periods.